Field behavior of potted seedlings of strawberry plants in different growing seasons - Becker, Tais Barbosa; Gonçalves, Michel Aldrighi; Ferreira, Leticia Vanni; Antunes, Luis Eduardo Correa (Emirates Journal of Food and Agriculture, 2020)
Since dependence on seedling importation has been a hindrance to strawberry farmers, production of national plants has become an alternative solution. This study aimed at evaluating the field behavior of potted seedlings of strawberry plants in a low tunnel system in different early growing seasons in Rio Grande do Sul, Brazil. The experiment was carried out at Embrapa Clima Temperado in 2015 and 2016 in a randomized block design, composed of a 4x3 factorial, four cultivars (Aromas, Camarosa, Festival and Oso Grande) and three growing seasons (March 16th, April 1st and April 16th). For all seasons, the cultivation was until November 30 in 2015 and October 31 in 2016. The following variables were determined: beginning and full blooming, beginning and length of harvest; number of fruits; mean fruit mass; and fresh mass per plant throughout early and total production. The cultivar Aromas presents lower flowering uniformity among plants (difference between beginning and full flowering) according to the two years of evaluation. Potted strawberry seedlings planted until early April 1st - Season 2 in Pelotas, RS, allow high early production, with production above 400 grams per plant. The cultivar Camarosa when planted on March 16 or April 1 had total yield per plant above 800 grams. All cultivars under study (Aromas, Camarosa, Festival and Oso Grande) have better plant development and higher total yield gains in years with higher temperature and lower rainfall in the initial phase and good rainfall distribution over the growing season. (2015) than in years with most frequent precipitation and lower temperature in the initial phase and poor rainfall distribution over the growing season (2016).